Slope stability analysis and stabilization : new methods and insight - Cheng, Y. M.; Lau, C. K. (Boca Raton, Florida : CRC Press / Taylor & Francis, 2014)
'This book provides a critical review of these and offers several more appropriate approaches for overcoming numerical convergence and the location of critical failure surfaces in two-dimensional and three-dimensional cases. New concepts in three-dimensional stability analysis, finite element analysis and the extension of slope stability problems to lateral earth pressure problems are also addressed. It gives helpful practical advice and design resources in the form of recommendations for good analysis and design practice, design charts and tables for the engineer.'--
Includes bibliographical references and index.
Keywords: Slopes (Soil mechanics).; Soil stabilization